2019
DOI: 10.3389/fonc.2019.01039
|View full text |Cite
|
Sign up to set email alerts
|

GDF11 Implications in Cancer Biology and Metabolism. Facts and Controversies

Abstract: Growth Differentiation Factor 11 (GDF11), a member of the super family of the Transforming Growth Factor β, has gained more attention in the last few years due to numerous reports regarding its functions in other systems, which are different to those related to differentiation and embryonic development, such as age-related muscle dysfunction, skin biology, metabolism, and cancer. GDF11 is expressed in many tissues, including skeletal muscle, pancreas, kidney, nervous system, and retina, among others. GDF11 cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 84 publications
0
28
0
Order By: Relevance
“…This controversy suggests that the functional roles of GDF11 are complicated, and revealing the fundamental role of endogenous GDF11 could provide clear clues for clarification of the GDF11 function. Growth differentiation factor 11 has been shown widely expressed in proliferative cells and tissues ( Zhang et al, 2018 ; Simoni-Nieves et al, 2019 ; Tito et al, 2019 ; Dai et al, 2020 ; Rochette et al, 2020 ). However, it is still unknown whether GDF11 plays a causal role in replicative cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This controversy suggests that the functional roles of GDF11 are complicated, and revealing the fundamental role of endogenous GDF11 could provide clear clues for clarification of the GDF11 function. Growth differentiation factor 11 has been shown widely expressed in proliferative cells and tissues ( Zhang et al, 2018 ; Simoni-Nieves et al, 2019 ; Tito et al, 2019 ; Dai et al, 2020 ; Rochette et al, 2020 ). However, it is still unknown whether GDF11 plays a causal role in replicative cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Growth differentiation factor 11 (GDF11, also known as bone morphogenetic protein 11, BMP11) is a member of transforming growth factor-beta (TGF-β) family. Accumulated evidence has shown that GDF11 is widely expressed in both the proliferative cells and tissues including the activated hepatic stellate cells of the liver ( Zhang et al, 2018 ; Dai et al, 2020 ; Rochette et al, 2020 ), keratinocytes and dermal fibroblasts of the skin ( Tito et al, 2019 ; Rochette et al, 2020 ), pancreas, skeletal muscle, kidney, retina, among others ( Simoni-Nieves et al, 2019 ), and postmitotic cells such as neurons of the central nervous system ( Hayashi et al, 2018 ). The expression of GDF11 in proliferative cells suggests its possible important functions in the proliferative cells ( Rochette et al, 2015 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…GDF11 has also previously been associated with aging in numerous studies; however, its exact pathophysiological role remains unclear [ 56 ]. Increased GDF11 has been associated with increased stemness [ 57 ], and CRC patients with increased expression of this genes have been shown to have reduced survival [ 58 ]. Silencing GDF11 in the CRC cell line Caco-2 has also implicated a role for this gene in proliferation [ 57 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased GDF11 has been associated with increased stemness [ 57 ], and CRC patients with increased expression of this genes have been shown to have reduced survival [ 58 ]. Silencing GDF11 in the CRC cell line Caco-2 has also implicated a role for this gene in proliferation [ 57 , 59 ]. These findings add further weight to the potential role of known lifestyle factors in EOCRC.…”
Section: Discussionmentioning
confidence: 99%
“…We identified CXCL13 and GDF11 as potential cytokines that could explain the influence of the BMSC on leukaemia cell proliferation and migration. The cytoattractive properties on B-cells 47 and the role in the regulation of different tumours 75-77 of CXCL13 have been described, while GDF11 has been discussed to be involved in ageing and the development of various cancers 78 . GDF11 also plays a role in bone development and remodelling 79 .…”
Section: Cxcl13 Levels In the Bmm Are Age-dependentmentioning
confidence: 99%